Pendidikan Jiwa Perspektif Ibnul Qayyim - Ahmada, Futiha Alambarra Amaan; Zubaidah, Citra; Rohimah, Siti (TSAQOFAH, 2024)
The lack of education about the values of life, character, spirituality, and morals, in an increasingly sophisticated and free age, has resulted in various problems and social offences, and criminality in society. The urgency of spiritual education is needed to prevent the adverse effects that occur due to these factors. One of the great figures and scholars who discuss mental education is Ibnul Qayyim. To obtain an overview of the mental education taught by Ibnul Qayyim, this research aims to explore what and how the concept of spiritual education by Ibnul Qayyim. By using a literature study approach, this qualitative research considers books, journals, articles, and written data both digital and print out as data sources. The analysis technique used is in the form of data reduction and display and then drawing conclusions. From this research, it is concluded that according to Ibnul Qayyim, soul education is an effort to educate the heart to the level of nafs muthmainnah which is obtained through devotion to Allah. The concept of spiritual education according to Ibn Qayyim is divided into two methods, namely the method of imaniyah education which is oriented towards instilling straight faith and khuluqiyah education which is oriented towards moral education and noble manners through exemplary. From these two methods will be formed an exemplary based on knowledge to achieve faith that is straight and in accordance with sharia. Therefore, teachers and educators are expected to be able to apply these two methods so that the learning provided is meaningful and can produce a generation that is noble and has character.